Designing and executing an implementation model of a project portal for a geographically distributed organization - Obed, Noli B. (University of the Philippines Diliman, 2012)
Big firms which operate in as big as a nationwide scale normally find it hard to manage critical knowledge amongst key people who are involved in different projects because of geographical hindrances and lack of facilities in properly and systematically managing these information. A good example of large firms that encounters such problems is a telecommunications firm which has its personnel practically dispersed all over the country. Relaying of knowledge or having vital project information available to the right people at the right time is normally done via traditional means such as emails or consolidating files in shared folders which could prove to be very difficult especially as the size of information increases and as it changes through time. This project addresses this concern by creating an implementation model of a project portal for a geographically distributed organization as applied in a telecommunications firm. The outputs of the project are an implementation model and an actual implemented project portal based on the implementation process created. The pilot project portal will be deployed and shall be used by a set of pilot users. A KM Self-Assessment Method was employed in this project to assess the organization's readiness and state of performing knowledge management. The result of the assessment was used to identify critical points where the organization can further improve on, particularly on those that can be addressed by employing the strategy of using project portals in handling their organizational knowledge. An assessment of the solution to be used for the portal implementation was conducted. The main criteria for tool selection were the availability of the basic features, ease of use, and availability of internal support for required customization and other relevant technical activities. Selection of tool from currently available applications in Company XYZ was prioritized. A standard implementation model for project portal requests was then laid out. Prior to this project, no formal means of requesting and processing is in place for project portal requests which means that the actual requesting, creation, up to launching of a project portal is done spontaneously by the requesting business unit and the knowledge management team. Formal documentations (forms) were also created that served as inputs to the different steps specified in the proposed implementation model. The implementation model is formed on the simplest approach scheme/linear approach. After creating a standard implementation model for project portal requests, the author, alongside a business analyst from another department simulated the whole process to test and create a pilot project portal for a particular service project. The author first discussed with the business analyst the rationale of the project and the need for them to go through the steps of the designed project portal implementation model. Upon selection of the service project that will be used as a test subject for the project portal creation process, the participants went through all the steps of the project portal implementation model. Guided by the standard implementation model with a standard set of forms that were used as inputs to the development and implementation of the requested project portal, the author, alongside the business analyst, was be able to create in a more efficient and effective way the project portal for the selected service project. The project was also able to create a generic portal template that can be used for other future service projects that shall require the use of project portals. As this implementation model is applied in other project categories like network projects, the knowledge management team can also develop other generic portal templates.